2014
DOI: 10.1158/1078-0432.ccr-14-0677
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Oxidative Stress in Rabbits with Papillomavirus-Associated Head and Neck Cancer Induces Tumoricidal Immune Response That Is Adoptively Transferable

Abstract: Purpose: How tumors evade or suppress immune surveillance is a key question in cancer research, and overcoming immune escape is a major goal for lengthening remission after cancer treatment. Here, we used the papillomavirus-associated rabbit auricular VX2 carcinoma, a model for studying human head and neck cancer, to reveal the mechanisms underlying the antitumorigenic effects of intraperitoneal oxidative stressExperimental Design: Solid auricular VX2 tumors were induced in immune-competent adult New Zealand W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 51 publications
(57 reference statements)
1
32
0
Order By: Relevance
“…The induction of antiviral cytokines such as IFN and the modulation of pro-inflammatory cytokines as IL-6, have been demonstrated by ozonating blood such as major autohemotherapy (MAH). Although ozone is a weak inducer, reinfused lymphocytes and monocytes during mayor autohemotherapy (MAH), can migrate through the lymphoid system, and activate other cells that, in time, will lead to the stimulation of the immune system [32,34]. This may represent an important process because it is known that an acute viral disease becomes more severe because the virus is particularly virulent, the heterogeneous viral population evolves rapidly and escapes immune control, or because the immune system becomes tolerant to viral antigens and becomes unable to counteract the infection.…”
mentioning
confidence: 99%
“…The induction of antiviral cytokines such as IFN and the modulation of pro-inflammatory cytokines as IL-6, have been demonstrated by ozonating blood such as major autohemotherapy (MAH). Although ozone is a weak inducer, reinfused lymphocytes and monocytes during mayor autohemotherapy (MAH), can migrate through the lymphoid system, and activate other cells that, in time, will lead to the stimulation of the immune system [32,34]. This may represent an important process because it is known that an acute viral disease becomes more severe because the virus is particularly virulent, the heterogeneous viral population evolves rapidly and escapes immune control, or because the immune system becomes tolerant to viral antigens and becomes unable to counteract the infection.…”
mentioning
confidence: 99%
“…The animal experiment was approved by the Regional Board Giessen, Germany [V54-19c20-15(1) MR20/26 Nr.34/2011] according to the German Animal Protection Law. Auricular tumors were experimentally induced by inoculation of a VX2 tumor cell suspension as described previously (11). Auricular VX2 tumor samples were randomly taken from two adult male Iffa Credo New Zealand White rabbits (Charles River Wiga Deutschland GmbH, Sulzfeld, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…For nearly 20 years, the auricular VX2 carcinoma of the New Zealand White (NZW) rabbit serves as an animal model for human head and neck squamous cell carcinomas (HNSCC) (1). Our previous studies (2,3) demonstrated the suitability of the VX2 carcinoma as a model system for HPV associated HNSCC since this tumor, similarly to HPV + HNSCC, is the consequence of a papillomavirus (cottontail rabbit papilloma virus, CRPV) infection. Against this background it is of utmost importance to develop a VX2 carcinoma derived cell line to be able to perform in vitro studies with this animal model.…”
Section: Figure 3 Characterization Of the Vx2 Cell Line By Flow Cytomentioning
confidence: 99%